Factors that influence job satisfactions among employees in Assembly Services Sdn Bhd (ASSB) / Nur Amirah Aqilah Faisal and Rahaizah Md Tap - Faisal, Nur Amirah Aqilah; Md Tap, Rahaizah (2014)
Employees satisfaction plays a vital role in the success most of the organizations. This study work attempts to evaluate what are the factors that influenced the increases of job satisfaction among Assembly Services Sdn Bhd (ASSB). The previous study has shown that, there was a correlation between an employee’s satisfaction and the achievement of the organizations. Because of that, this research paper highlights some of these problems and presents a picture of level of job satisfaction among employees of ASSB company. It also identifies unique issues of job satisfaction in the companies. ASSB is selected for the research because they are currently undergoing continued expansion. In order to gain competitive advantage and adapt to the dramatic changing environment, it is important for them to achieve management efficiency by increasing employee’s satisfaction in ASSB. Also, it was conducted for the purpose to find the relationship between these variables. It will be analyzed and examined by using four major independent variables which are monetary/ salary, working conditions, interpersonal relationship and promotion. The conclusion drawn from this study are the major sources of job satisfaction for ASSB employees are shown to be monetary/ salary, promotion, working condition and interpersonal relationship. In addition, the overall job satisfaction of the employees in ASSB is at the positive level.